2010
DOI: 10.11301/jsfe.11.51
|View full text |Cite
|
Sign up to set email alerts
|

The Visualization and Quantification of the Flow in the Pan During Induction Heating and Gas Heating

Abstract: In cooking that there are solid foods in soup, natural convection flow in a pan may affect food quality. This study shows the visualization and quantification of the flow in the pan using developed new tracer particle during the induction heating (IH) and the gas heating. Development of the tracer particle imitated the method of making an artificial salmon roe. The density of the tracer particle could be adjusted to be the same as water. The average diameter of the tracer particle was 2.5 mm when the tracer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The surface temperature of the pan during heating over each cooker was visualized using a thermal imager (NEC San-ei Instruments, Ltd., TH9100WLN). (14) The results were in agreement with those reported by Kawakami et al; (15) the entire pan surface, including the bottom and side, was heated by the gas stove, whereas only part of the bottom of the pan over the coil was heated by the IH cooker. (14) On the basis of these observations, the heating methods using the gas and IH cookers are referred to as "pan surface heating" and "local heating", respectively.…”
Section: Methodssupporting
confidence: 90%
“…The surface temperature of the pan during heating over each cooker was visualized using a thermal imager (NEC San-ei Instruments, Ltd., TH9100WLN). (14) The results were in agreement with those reported by Kawakami et al; (15) the entire pan surface, including the bottom and side, was heated by the gas stove, whereas only part of the bottom of the pan over the coil was heated by the IH cooker. (14) On the basis of these observations, the heating methods using the gas and IH cookers are referred to as "pan surface heating" and "local heating", respectively.…”
Section: Methodssupporting
confidence: 90%
“…Figure 7 shows histograms quantifying the flow velocity distribution in the pots. Regarding the magnitude of flow velocity, Kawakami et al (2010, 2013) measured the average velocity of tracer particles when 20 L of water was placed in a pot and heated by gas fire. They reported that the range of flow velocity after approximately 6 min was approximately 0.5–2 × 10 −2 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…Elsaady et al (2023) simulated water temperature distribution using an industrial heating system and evaluated the effect of susceptor materials on the water temperature. In terms of large-scale cooking, Kawakami et al (2010Kawakami et al ( , 2013 measured the temperature, heat flux, and flow velocity in a pot filled with 20 L of water and heated by gas fire and an induction heater. They employed the measured heat flux at the wall of the pan as a boundary condition for the CFD analysis and reported that at high heating temperatures, the flow velocities under both heating types become similar.…”
Section: Introductionmentioning
confidence: 99%